List, listopad, literatura : Miniatura biograficzna Anny Frajlich .......... 85 - Madejski, Jerzy (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
A LETTER, NOVEMBER, LITERATURE: THE BIOGRAPHIC MINATURE OF ANNA FRAJLICHThe essay focuses on biographical themes in Anna Frajlich’s work, examples of which can befound in various books and literary forms. The art of Frajlich’s life-writing is demonstratedbased on the analysis of the poem Nad listami Brunona Schulza [‘Reading the Lettersof Bruno Schulz’] from the volume entitled “Between Dawn and the Wind”. The poeticportrait of the Polish writer becomes an opportunity to show the esthetic of Bruno Schulz,as well as to understand the literature of Anna Frajlich.